Importance of human papillomavirus infection in squamous cell carcinomas of the tongue in Guangdong Province, China. Issue 1 (January 2020) - Huang, Kunsong; Ni, Guoying; Ma, Bowei; Chen, Shu; Luan, Yi; Wang, Tianfang; Walton, Shelley; Frazer, Ian; Liu, Xiaosong; Pan, Xuan
Objective: Tongue squamous cell carcinoma is one of the most common oral tumors. Human papillomavirus (HPV) infection has been proposed as a risk factor for head and neck squamous cell carcinoma, particularly oropharyngeal squamous carcinoma. Methods: In this study, we retrospectively analyzed HPV infection in 121 Chinese patients with tongue squamous cell carcinoma in Guangdong Province. Polymerase chain reaction of HPV DNA and immunohistochemistry staining of p16 protein were used to identify the presence of HPV in formalin-fixed paraffin-embedded samples. Results: HPV DNA was detected in 15.7% (n = 19) of tongue squamous cell carcinoma patients, with HPV16 being the most common type (n = 8, 42.1%). p16 staining did not correlate with detection of HPV DNA. Male sex was associated with HPV-positive tongue squamous cell carcinoma, whereas there were no significant differences in alcohol consumption, smoking, or age when tumors were stratified by HPV. Conclusion: Our study showed that HPV infection contributed to tongue squamous cell carcinoma in a small cohort of patients in Guangdong Province, China. Further investigation is needed to confirm whether HPV is a causal factor for tongue squamous cell carcinoma.